INTERNAT DALAM PERSPEKTIF NASIONALIS DAN PROSPEKNYA DI ACEH: KAJIAN EKSPLORATIF PEMIKIRAN SATI’ AL-HUSAIRI DAN SUTOMO - Gunawan Adnan (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2012)
This article aims at explaining Sati 'al-Husairi and Sutomo thoughts on internat. The writing is based on the assumption that the figures other than as proponent of the eastern nationalism, also as thinkers of education. According to them, the internat is a form of an ideal education institution to encourage the youth of a nation. The results of the study shows that Sati 'al-Husairi’s thought is simply influenced by Fichte’s. Whilst the thought of Sutomo, moreover is being influenced by Fichte’s and gets in touch with Javanese boarding school tradition as well. The thought of these two figures on the internat is still relevant in Aceh to be used as a fortress upon the anytime Indonesian nationalism emergence.